Indigeneity of transport in developing cities. Issue 2 (2nd April 2016) - Mateo-Babiano, Iderlina
ABSTRACT: This paper offers an alternative conceptualization of informality within the transport sector. While it shows that informal transport is a far from trivial component of urban economies, it also highlights the sometimes problematic use of informality to homogeneously describe various public transport modes within the Southeast Asian transport landscape. It initially reviews a number of contested assumptions in the informality discourse within the context of public transportation in developing cities. It then proposes the concept of indigenous transport as a potential alternative, arguing that such perspective may better acknowledge and describe the mode's local and vernacular qualities as well as its complementary and supplementary functions. For the purposes of this paper, indigenous transport is described to pertain to those modes that respond to local demand, evolved based on local conditions and endemic to local mobility cultures. The indigenous transport framework aims to elucidate the five key characteristics of indigenous transport modes from a transport user's perspective. This is supported by an empirical study conducted in three Southeast Asian developing cities of varying geographical scales, namely Baguio (Philippines), Bandung (Indonesia) and Ho Chi Minh (Vietnam) to provide evidence that a transport user's prism will and can authentically present an alternative version of informality, and assist in painting an overall picture of the role of indigenous transport within the transport system of developing cities.